Carry-over coarticulation in joint angles - Hansen, Eva; Grimme, Britta; Reimann, Hendrik; Schöner, Gregor (Experimental brain research, 2015)
Coarticulation indicates a dependence of a movement segment on a preceding segment (carry-over coarticulation) or on the segment that follows (anticipatory coarticulation). Here we study coarticulation in multidegrees of freedom human arm movements. We asked participants to transport a cylinder from a starting position to a center target and on to a final target. In this naturalistic setting, the human arm has ten degrees of freedom and is thus comfortably redundant for the task. We studied coarticulation by comparing movements between the same spatial locations that were either preceded by different end-effector paths (carry-over coarticulation) or followed by different end-effector paths (anticipatory coarticulation). We found no evidence for coarticulation at the level of the end-effector. We found very clear evidence, however, for carry-over, not for anticipatory coarticulation at the joint level. We used the concept of the uncontrolled manifold to systematically establish coarticulation as a form of motor equivalence, in which most of the difference between different movement contexts lies within the uncontrolled manifold that leaves the end-effector invariant. The findings are consistent with movement planning occurring at the level of the end-effector, and those movement plans being transformed to the joint level by a form of inverse kinematics. The observation of massive self-motion excludes an account that is solely based on a kinematic pseudo-inverse.